PO 32 - BONE CEMENT IMPLANTATION SYNDROME: A CASE REPORT - Beatriz Carvalho Gonçalves1,; Daniel Carvalho1,; Ricardo Rodrigues1,; Madalena Passos1, (Journal of the Portuguese Society of Anesthesiology, 2023)
.